Production of Biogas from Plantain Peels, Using Cow Dung as Substrate (British Journal of Multidisciplinary and Advanced Studies, 2024)
In a biodigester setup, the researchers investigated the production of methane gas using plantain peel and cow dung as substrates. Two buncher flasks, corks, a glass tube, and a calibrated conical flask comprised the biodigester setup. The setup involved anaerobic digestion processes, analyzing different ratios of cow dung and plantain peel to produce biogas. The main anaerobic digestion process was carried out in Buncher flask one, after which the methane gas formed was sent to Buncher flask two through a rubber tube, where the by-products such as carbon dioxide and hydrogen sulfide were absorbed from the methane gas and the refined biogas was stored in a storage tube. For this study, there were seven setups of cow dung and plantain peel in digester1, digester2, digester3, digester4, digester5, digester6, and digester7 in the ratios of 0g;100g(100%), 10g(10%): 90g(90%), 20g(20%): 80g(80%), 30g(30%): 70g(70%), 40g(40%): 60g(60%), and 50g (50%): 50g(50%), respectively. After 15 days of retention, the slurry with the highest yield is digester 1, with 574 ml/day. The obtained kinetic modeling indicates a rise in yield as the retention time increases. Furthermore, it was observed that continuous mixing boosted the biogas production yield. The results provided valuable insights into the potential for biogas production from agricultural and animal wastes through anaerobic digestion, highlighting the impact of functional groups on biogas yield.